Parental Internet-Specific Rules and the Onset of Adolescents' Problematic Social Media Use: Prospective Study Testing Potential Moderators - Geurts, Suzanne; Koning, Ina; Van den Eijnden, Regina; Vossen, Helen (JMIR Publications Inc., 2025)
BACKGROUND: Many parents are concerned about their adolescents' (problematic) social media use. Therefore, parents may apply restrictive mediation practices to prevent problematic social media use. However, their effectiveness remains unclear. OBJECTIVE: This study aimed to provide insights into the specific groups and conditions under which restrictive mediation may effectively prevent adolescents' problematic social media use. Specifically, we investigated the prospective relationship between rules about the amount, location, and timing of internet use and the onset of adolescents' at-risk or problematic social media use. In addition, we examined the moderating role of demographic and parenting factors, including adolescents' age, adolescents' gender, adolescent involvement in rule-setting, positive parenting, parental phubbing, and quality of coparenting (2-way interactions). Furthermore, we explored whether the moderation effects of the parenting factors varied by adolescents' age and gender (3-way interactions). METHODS: Four-wave survey data of 315 adolescents (T1: mean age 13.44, SD 2.26 years; n=146, 46.3% girls, n=169, 53.7% boys) and their parents (T1: mean age 46.4, SD 5.05 years; n=292, 55.4% mothers) were used. Data were collected between April 2020 and January 2022, with a 6-month interval between each wave. RESULTS: No significant main effect was found of internet-specific rule-setting at T1 on the onset of adolescents' at-risk or problematic social media use throughout the study period (odds ratio [OR] 0.959, 95% CI 0.60-1.54, d=0.02). Yet, 2-way interaction analyses revealed that the effect of internet-specific rule-setting varied by adolescents' age (OR 2.171, 95% CI [1.35-3.49], d=0.43). Specifically, for adolescents aged <12.31 years (-0.5 SD), stricter rules were associated with a lower likelihood of developing at-risk or problematic social media use (unstandardized beta (B)=-0.568, SE=0.280, 95% CI [-1.12 to -0.02], P=.042). In contrast, for adolescents aged >15.70 years (+1 SD), stricter rules were associated with a higher likelihood of developing at-risk or problematic social media use (B=0.594, SE=0.294, 95% CI 0.02-1.17, P=.043). Two-way interaction effects of rule-setting with adolescents' gender (OR 0.945, 95% CI 0.54-1.64, d=0.03), adolescent involvement in rule-setting (OR 1.02, 95% CI 0.77-1.36, d=0.01), positive parenting (OR 1.044, 95% CI 0.69-1.59, d=0.02), parental phubbing (OR 0.977, 95% CI [0.72-1.33], d=0.01), and quality of coparenting (OR 0.877, 95% CI 0.64-1.21, d=0.07) were not significant, nor were any of the 3-way interaction effects. CONCLUSIONS: Setting internet-specific rules seems to have a preventive effect on the development of problematic social media use symptoms in pre- and early adolescence, but may be counterproductive from the age of 15.7 years onward. These findings highlight the importance of age-appropriate parental mediation strategies to prevent problematic social media use.
Keywords: Adolescent; Adolescent Behavior; Female; Humans; Internet; Internet Addiction Disorder; Internet Use; Male; Middle Aged; Parent-Child Relations; Parenting; Parents/psychology; Prospective Studies; Social Media; Surveys and Questionnaires